2023
DOI: 10.1002/hsr2.1194
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laparoscopic versus open inguinal hernia repair for inguinal hernia treatment: A retrospective cohort study

Abstract: Objectives Although laparoscopic inguinal hernia repair (LIHR) has been widely accepted for treating inguinal hernia, the procedure remains very technical and challenging. The present study aimed to assess the effect of LIHR in relation to operation time, intraoperative hemorrhage and postoperative hospitalization. Methods A total of 503 patients with inguinal hernia admitted at the Wuxi Rehabilitation Hospital between June 2019 and July 2021 were included in this retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that surgeons need to go through a special learning curve from basic operations to pro ciency in mastering LIHR techniques [30] . Other medical centers have reported a range of 50 to 250 cases [31] , while our center recently reported 54 cases as well [9] . All patients this study were completed by the same group of senior and professional surgeons.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies have shown that surgeons need to go through a special learning curve from basic operations to pro ciency in mastering LIHR techniques [30] . Other medical centers have reported a range of 50 to 250 cases [31] , while our center recently reported 54 cases as well [9] . All patients this study were completed by the same group of senior and professional surgeons.…”
Section: Discussionmentioning
confidence: 54%
“…Laparoscopic inguinal hernia repair (LIHR) and open inguinal hernia repair (OIHR) procedures are often compared during the 20 years [4,[6][7][8][9] . Importantly, with the advantages of minimally invasive technology, such as reduced wound complications, less recurrence rate, and faster recovery, which is highly favored by not only surgeons, but also patients [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic hernia surgery shows various advantages over open inguinal hernia surgery (7)(8)(9), including lower operation times, early recovery, and fewer complications (10). However, the choice between TEP and TAPP remains unclear (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“… 30 Other medical centers have reported a range of 50 to 250 cases, 31 while our center recently reported 54 cases as well. 9 All patients in this study were completed by the same group of senior and professional surgeons. Perhaps, the LIHR approach could be performed easier by exerted surgeons after overcoming the laparoscopic technical learning curve, thereby significantly shortening the operative time, which in this study was similar to that of the OIHR group.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Laparoscopic inguinal hernia repair (LIHR) and open inguinal hernia repair (OIHR) procedures are often compared during the 20 years. 4,[6][7][8][9] Importantly, with the advantages of minimally invasive technology, such as reduced wound complications, less recurrence rate, and faster recovery, which is highly favored by not only surgeons but also patients. 10 However, no prospective studies have reported the correlation between age, surgical methods (LIHR and OIHR), and surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%